Factors Affecting the Reproductive Performance Efficiency of Beef Cattle in the South Sulawesi Province - alim, iqbal; Priyanto, Rudy; Jakaria, Jakaria (Fakultas Peternakan, Universitas Padjadjaran, 2023)
The application of artificial insemination (AI) technology continues to improve, especially in South Sulawesi, one of Indonesia's beef cattle population centers. This study aims to determine the factors influencing AI implementation in South Sulawesi. Reproduction performance secondary data was obtained from iSIKHNAS. Data were tabulated by district, inseminator, cattle breed, and reproductive variables (S/C value and pregnancy percentage). Data were analyzed using descriptive, variance, and correlation analyses. Bali, Limousin, and Simmental cattle had S/C of 2.24, 2.44, and 2.61, respectively. Different district locations have better S/C (P<0.05), such as Palopo, Barru, Sidenreng Rappang, Jeneponto, North Luwu, Sinjai, Bantaeng, and Tana Toraja. The performance of inseminators had a significant effect (P<0.05). Although with a low number of inseminators, Tana Toraja had the best reproductive efficiency, compared to Soppeng, which has many inseminators but low livestock reproductive efficiency (P<0.05). In conclusion, reproductive efficiency performance is influenced by location (district topography) and inseminator performance, whereas the breed of cattle does not affect S/C values and pregnancy percentage. The results of the correlation analysis showed that S/C has a positive correlation with inseminator performance of 44.3%.